Jacques Pépin: art of the chicken : a master chef's paintings, stories, and recipes of the humble bird - Pépin, Jacques (Harvest, an imprint of William Morrow, 2022)
From legendary chef Jacques Pepin, a book celebrating his lifelong love of chickens, featuring dozens of his celebrated paintings and more than 50 recipes, along with a treasure trove of poignant and often humorous stories.